Strategi Pengembangan dan Pengelolaan Pariwisata Kabupaten Simalungun - Lasmaria Situmorang; Hisarma Saragih; Anggiat Sinurat (CV. ULIL ALBAB CORP, 2024)
This research aims to analyze the Simalungun Regency Tourism Development and Management Strategy. The research method used is qualitative descriptive analysis. To find out the handling strategy, use Strengths, Weakness, Opportunities, Threats (SWOT) analysis. The results of research on tourism management and development strategies in Simalungun Regency are on the strategy of strengths and opportunities by improving the quality of infrastructure to support tourism development. Maximizing the management of tourism potential. Optimizing community participation in preserving nature. Improving the performa nce of tourism managers by completing socio-economic facilities to support increased community activity in carrying out tourist visits. In developing tourist attractions, it is necessary to maximize the role of stakeholders in developing tourism potential and preserving nature in order to maximize tourism development. The active role of relevant agencies, especially in the tourism sector, tourism industry managers and local communities is very necessary by maintaining hospitality for tourists so as to have a positive impact on tourism development.